Activation of homologous recombination in G1 preserves centromeric integrity - Yilmaz, Duygu; Furst, Audrey; Meaburn, Karen; Lezaja, Aleksandra; Wen, Yanlin; Altmeyer, Matthias; Reina-San-Martin, Bernardo; Soutoglou, Evi (Nature (London), 2021)
Centromeric integrity is key for proper chromosome segregation during cell division 1 . Centromeres have unique chromatin features that are essential for centromere maintenance 2 . Although they are intrinsically fragile and represent hotspots for chromosomal rearrangements 3 , little is known about how centromere integrity in response to DNA damage is preserved. DNA repair by homologous recombination requires the presence of the sister chromatid and is suppressed in the G1 phase of the cell cycle 4 . Here we demonstrate that DNA breaks that occur at centromeres in G1 recruit the homologous recombination machinery, despite the absence of a sister chromatid. Mechanistically, we show that the centromere-specific histone H3 variant CENP-A and its chaperone HJURP, together with dimethylation of lysine 4 in histone 3 (H3K4me2), enable a succession of events leading to the licensing of homologous recombination in G1. H3K4me2 promotes DNA-end resection by allowing DNA damage-induced centromeric transcription and increased formation of DNA–RNA hybrids. CENP-A and HJURP interact with the deubiquitinase USP11, enabling formation of the RAD51–BRCA1–BRCA2 complex 5 and rendering the centromeres accessible to RAD51 recruitment and homologous recombination in G1. Finally, we show that inhibition of homologous recombination in G1 leads to centromeric instability and chromosomal translocations. Our results support a model in which licensing of homologous recombination at centromeric breaks occurs throughout the cell cycle to prevent the activation of mutagenic DNA repair pathways and preserve centromeric integrity. Centromeres are able to recruit the homologous recombination machinery during G1 via CENP-A and HJURP, thereby preserving centromeric integrity even in the absence of a sister chromatid.